Integrated use of the GeneXpert Platform for TB, HIV and EVD Testing in Liberia (Global Journal of Medical Research, 2020)
Background: The capacity for molecular testing of the Human Immunodeficiency Virus (HIV) Viral load, Tuberculosis (TB) and epidemic- prone disease was very limited in Liberia prior to the Ebola Virus Diseases (EVD) outbreak. The use of point of care and near point of care machines for multiple disease testing of HIV, TB and EVD was adopted as a solution to these challenges. The purpose of this study was to evaluate the integrated use of GeneXpert for the three disease testing. Methods: A previously collected and reported GeneXpert testing data was used to evaluate the integrated use of the GeneXpert platform for TB, HIV viral load and EVD testing. All the laboratory GeneXpert secondary data available since the machines were installed and started testing were analyzed.
Keywords: GeneXpert; EVD; HIV; viral load; TB